Biocatalytically active microgels by precipitation polymerization of N-isopropyl acrylamide in the presence of an enzyme. Issue 49 (9th September 2019) - Reinicke, Stefan; Fischer, Thilo; Bramski, Julia; Pietruszka, Jörg; Böker, Alexander
Abstract : Precipitation polymerization of NIPAm in the presence of an enzyme and a protein-binding comonomer as a simple and versatile immobilization protocol. Abstract : We present a novel protocol for the synthesis of enzymatically active microgels. The protocol is based on the precipitation polymerization of N -isopropylacrylamide (NIPAm) in the presence of an enzyme and a protein binding comonomer. A basic investigation on the influence of different reaction parameters such as monomer concentration and reaction temperature on the microgel size and size distribution is performed and immobilization yields are determined. Microgels exhibiting hydrodynamic diameters between 100 nm and 1 μm and narrow size distribution could be synthesized while about 31–44% of the enzyme present in the initial reaction mixture can be immobilized. Successful immobilization including a verification of enzymatic activity of the microgels is achieved for glucose oxidase (GOx) and 2-deoxy-d -ribose-5-phosphate aldolase (DERA). The thermoresponsive properties of the microgels are assessed and discussed in the light of activity evolution with temperature. The positive correlation of enzymatic activity with temperature for the GOx containing microgel originates from a direct interaction of the enzyme with the PNIPAm based polymer matrix whose magnitude is highly influenced by temperature.